Observation of Arctic island barren-ground caribou (Rangifer tarandus groenlandicus) migratory movement delay due to human induced sea-ice breaking - Dumond, Mathieu; Sather, Shane; Harmer, Rob (Rangifer, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The seasonal migration of the Dolphin and Union caribou (Rangifer tarandus groenlandicus) herd between Victoria Island and the mainland (Nunavut/Northwest Territories, Canada) relies on the formation of sea-ice that connects the Island to the mainland from late-October to early-June. During an aerial survey of the Dolphin and Union caribou herd in October 2007 on southern Victoria Island, Nunavut, Canada, we documented the short-term effects of the artificial maintenance of an open water channel in the sea-ice on caribou migratory movements during staging along the coast.